IJARAH AL-A'MAL DIFFERENTIATION OF RICE FARMING WORKERS ISLAMIC LEGAL PERSPECTIVE - Yuniartik Yuniartik (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Muamalah is a sharia law that regulates humans in relation to worldly affairs in social interactions in obtaining and developing assets. Muamalah that often occurs is in the case of cooperation between humans, where one party is a service provider or laborer, commonly called a laborer or worker, and the other party who provides a job or work area is called a service provider to carry out production activities provided that the worker or employee receives the job. Compensation in the form of wages. This collaboration with fiqh literature is called the ijarah al-a'mal contract, namely the rental of human services. This study aims to determine how the practice of distinguishing the ijarah al-a'mal of rice farm workers in terms of Islamic law. This type of research is a field research with an empirical sociological approach. The results of this study indicate that the practice of distinguishing ijarah al-A'mal of rice farm workers in terms of Islamic law if it is associated with the concept of muamalah, then the practice of paying rice farm workers who are paid in cash is in accordance with Islamic law because the pillars and conditions of wages have been met. However, the practice of working wages for rice farm workers whose payments are deferred is not in accordance with Islamic law because their wages are deferred until the harvest is complete and this is contrary to the hadith of the Prophet Muhammad regarding the time of payment of wages, besides that the pillars and conditions are not fulfilled, namely about ujrah (wages), because they have denied the pillars of wages, namely consent and qabul. The conclusion of this study is that the practice of Ijarah Al-A'mal Differentiation of Paddy Farmers from an Islamic Law Perspective where the payment of wages is initially paid with rice is then replaced with money without an agreement and deferred payment is makruh. Things that have become habits should be used as useful demands to avoid or leave these actions.